2018
DOI: 10.1111/iwj.12967
|View full text |Cite
|
Sign up to set email alerts
|

An evidence‐based review of split‐thickness skin graft donor site dressings

Abstract: This evidence-based review aimed to identify and evaluate current existing evidence relating to the efficacy of dressing materials for spit-thickness skin graft donor site wounds in relation to promoting rapid healing and reducing patient pain. A comprehensive systematic search of the literature between 2006 and 2016 identified 35 publications that were included in the review. Based on the results of the review, it was found that moist wound-healing products have a clear advantage over non-moist products in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…At present, wound dressings are expected to cover the wound and accelerate the healing process (Vowden and Vowden, 2014). Traditional dressings, also termed inert dressings (gauze, cotton pads, and bandages), are the most widely used clinical dressings owing to their low cost and simple manufacturing process (Broughton et al, 2006). However, several shortcomings limit their application, such as difficulty to maintain the wound bed moist and proneness to adhesion to granulation tissue (Moore and Webster, 2013).…”
Section: Wound Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, wound dressings are expected to cover the wound and accelerate the healing process (Vowden and Vowden, 2014). Traditional dressings, also termed inert dressings (gauze, cotton pads, and bandages), are the most widely used clinical dressings owing to their low cost and simple manufacturing process (Broughton et al, 2006). However, several shortcomings limit their application, such as difficulty to maintain the wound bed moist and proneness to adhesion to granulation tissue (Moore and Webster, 2013).…”
Section: Wound Dressingsmentioning
confidence: 99%
“…Acute wound pain has been shown to increase patient stress and subsequently negatively affect quality of life and lead to delayed wound healing (Broadbent et al, 2003). An evidence-based review summarizes the current evidence that wet wound healing dressing products have clear clinical advantages over non-wet dressing products in treating SSG donor site wounds (Brown and Holloway, 2018). However, no clear trend was detected regarding the performance of each dressing type.…”
Section: Split-thickness Skin Grafting (Ssg)mentioning
confidence: 99%
“…Hydrocolloid dressings are used as primary or secondary dressings for the management of pressure ulcers, chronic venous ulcers, diabetic foot ulcers, burns, partial thickness wounds, and splitthickness skin graft donor site wounds with various degrees of effectiveness (de Vries, 2018;Brown and Holloway, 2018). However, there is limited evidence that they are more effective than other dressings, particularly in managing diabetic foot ulcers (Dumville et al, 2013b) or pressure ulcers (Pott et al, 2014).…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%
“…Closed moist dressings are further claimed to lower the risk of contamination from the surroundings [63]. Five systematic reviews on donor site dressings were found and in four of them the authors conclude that a moist wound environment is associated with better outcomes, as in faster re-epithelialisation, less pain, and fewer infections [30,[64][65][66][67].…”
Section: Dressing Treatmentsmentioning
confidence: 99%